Does class size matter in postgraduate education?. (27th October 2019) - Gaggero, Alessio; Haile, Getinet
Abstract: The paper examines the impact of class size on postgraduate (PG) grades using administrative data from one of the largest Schools of a Russell Group University in the UK. As well as estimating fixed effects models on the population of PG candidates in the School, we exploit a policy change aimed at reducing class size to implement a regression discontinuity design. We find that class size does impact overall grades adversely; and the policy aimed at reducing class size impacts grades favourably. Our findings are robust to alternative specifications as well as being supported by the validity tests we conducted.